Recuerdo y memoria, componentes esenciales en tres cuentos de Juan José Saer - Mellerup, Susana Ester (Diálogos Latinoamericanos, 2015)
Memory is probably one of the most important and hotly debated of our mental functions and as such it is the subject of many different theoretical viewpoints, an object of study upon which a wide variety of analytical tools have been used, including psychoanalysis, neurology, literature, etc. In this essay, I will examine the work of literary author Juan José Saer, many of whose narrative fictions have memory (memoria) and recollection (recuerdo) as central themes. I will investigate the role of memory and recollection in some of Saer’s narratives, and at the same time explore conventional assumptions about the relation between past, present, and future, as seen through the lens of memory and recollection. I will approach the topic first from the point of view of semiotician Per Aage Brandt and later employing the theoretical work of Tzvetan Todorov’s “Los abusos de la Memoria”, Antonio Muñoz Molina’s “Memoria y Ficción” and José Antonio Marina’s “La memoria Creadora”.